Unveiling the Past: LiDAR Technology's Role in Discovering Hidden Ar-chaeological Sites - Simbolon, Roma Sinta; Comer, Alday (Jurnal Ilmu Pendidikan dan Humaniora, 2023)
This research delves into the transformative role of LiDAR (Light Detection and Ranging) technology in archaeological exploration, with a primary focus on the discovery of hidden archaeological sites. LiDAR has emerged as a game-changing tool, offering unprecedented advantages in the field, including rapid data collection, the penetration of coverings and vegetation, and a non-invasive approach to archaeological research. Through this technology, a multitude of hidden archaeological features, such as lost cities, intricate urban planning, extensive road networks, agricultural practices, and defensive structures, have been unveiled. These discoveries have rewritten historical narratives, reshaped our understanding of the past, and underscored the significance of cultural heritage preservation and sustainable land use practices. LiDAR's efficiency and accuracy have enhanced the speed and precision of data collection, making it an essential tool for future archaeological studies. Its non-invasive nature respects the integrity of archaeological sites, and its multidisciplinary collaborations expand the horizon of research. The recognition of the cultural and spiritual significance of hidden archaeological sites, particularly in indigenous regions, has influenced future research approaches. Insights into ancient agricultural practices and sustainable land use have the potential to guide contemporary practices and environmental conservation. LiDAR technology continues to evolve, promising even more efficient and accurate data acquisition, thereby further deepening our understanding of the past and enhancing the future of archaeological research.